Creation and Execution of a Novel Anesthesia Perioperative Care Service at a Veterans Affairs Hospital. (November 2017) - Alvis, Bret D.; King, Adam B.; Pandharipande, Pratik P.; Weavind, Liza M.; Avila, Katelin; Leisy, Philip J.; Ajmal, Muhammad; McHugh, Michael; Keegan, Kirk A.; Baker, David A.; Walia, Ann; Hughes, Christopher G.
Abstract : Physician-led perioperative surgical home models are developing as a method for improving the American health care system. These models are novel, team-based approaches that help to provide continuity of care throughout the perioperative period. Another avenue for improving care for surgical patients is the use of enhanced recovery after surgery pathways. These are well-described methods that have shown to improve perioperative outcomes. An established perioperative surgical home model can help implementation, efficiency, and adherence to enhanced recovery after surgery pathways. For these reasons, the Tennessee Valley Healthcare System, Nashville Veterans Affairs Medical Center created an Anesthesiology Perioperative Care Service that provides comprehensive care to surgical patients from their preoperative period through the continuum of their hospital course and postdischarge follow-up. In this brief report, we describe the development, implementation, and preliminary outcomes of the service. Abstract : Published ahead of print June 16, 2017.